Identification of Repellent and Insecticidal Constituents from Artemisia mongolica Essential Oil against Lasioderma serricorne - Chunxue You; Shanshan Guo; Wenjuan Zhang; Kai Yang; Zhufeng Geng; Shushan Du; Chengfang Wang; Zhiwei Deng (Journal of Chemistry)
The aims of this research were to determine the chemical composition and insecticidal and repellent activities of the Artemisia mongolica essential oil against Lasioderma serricorne and to isolate active constituents from the essential oil. The essential oil of A. mongolica was obtained by hydrodistillation and 36 components were identified with GC-MS. Eucalyptol (39.88%), (S)-cis-verbenol (14.93%), 4-terpineol (7.20%), (−)-camphor (6.02%), and α-terpineol (4.20%) were found to be major components. With a further isolation process, five constituents obtained from the essential oil were identified as eucalyptol, verbenol, 4-terpineol, camphor, and α-terpineol. In the progress of assay, it showed that L. serricorne adults had different sensitivities to the crude essential oil and isolated constituents. 4-Terpineol exhibited strongest contact activity against L. serricorne, showing the LD50 value of 8.62 μg/adult. Moreover, camphor and α-terpineol showed stronger fumigant activity (LC50=2.91 and 3.27 mg/L air, resp.) against L. serricorne than crude essential oil and other constituents. In addition, the essential oil, eucalyptol, verbenol, and α-terpineol showed comparable repellency against L. serricorne adults. The results indicate that the essential oil and isolated compounds have potential to provide more efficient and safer natural insecticides or repellents for control of insects in food and Chinese medicinal materials preservation.